MEMPERSIAPKAN RISIKO JANGKA PANJANG UNTUK MENINGKATKAN KUALITAS KINERJA KEUANGAN PADA PERIODE SELANJUTNYA - Arianto, Novita; Sari, Shinta Permata (ITB AAS Indonesia Surakarta, 2024)
Investments in property and real estate often fail due to immature investment analysis, especially analysis of various long-term risks that may occur, one of which is caused by errors in choosing the type of funding. This condition is definitely essential to be cognizant of in order to minimize potential risks through appropriate risk management and choose the most sensible investment option. The aim of this research is to determine the influence of solvency risk, credit risk and market risk on the financial performance of property and real estate companies listed on the Indonesia Stock Exchange for the 2019-2022 period. This research is a type of quantitative research using secondary data. The sampling technique used purposive sampling technique and obtained 69 observation samples. The data analysis method used is multiple linear regression analysis. The research results show solvency risk and market risk have influence on financial performance, while credit risk has insignificant influence on financial performance. Keywords : financial performance, solvency risk, credit risk, market risk